Climate-related flood risk to residential lending portfolios in Canada - Craig Johnston; Geneviève Vallée; Hossein Hosseini; Brett Lindsay; Miguel Molico; Marie-Christine Tremblay; Aidan Witts (Bank of Canada, 2023)
We assess the potential financial risks of current and projected flooding caused by extreme weather events in Canada. We focus on the residential real estate secured lending (RESL) portfolios of Canadian financial institutions (FIs) because RESL portfolios are an important component of FIs' balance sheets and because the assets used to secure such loans are immobile and susceptible to climate-related extreme weather events. We build a loan-level dataset from the residential RESL portfolios of some federally and provincially regulated FIs. We use current and projected flood events under different climate scenarios to apply shocks to these portfolios. We then control for private flood insurance using data from a variety of property and casualty insurers based in Canada. We find that the direct damages of flooding have modest impacts on the FIs' loss given default on their residential RESL portfolios. This is partly due to rising homeowner equity and the recent rapid increase in house prices across Canada. Nevertheless, some risk channels have emerged. Notably, the combined influence of high household leverage and lending in flood zones can exacerbate the risk that lenders face from extreme weather events. Our analysis also shows that other disaster-related risk channels may increase risk to lenders. These channels include climate change, price adjustment of the salvage value and time to settlement. However, this analysis has several limitations. Specifically, the lack of granular flood data may have led to an underestimation and smoothing of financial risks across households. As a result, the analysis potentially smoothed what could be more acute shocks to specific properties.
Keywords: C81; G21; Q54; 330; Climate change; Central bank research; Credit risk management; Econometric and statistical methods; Financial institutions; Financial stability